In Situ Spectroscopy of Calcium Fluoride Anchored Metal–Organic Framework Thin Films during Gas Sorption - Mandemaker, Laurens D. B. (Angew Chem Int Ed Engl, 2020)
Surface‐mounted metal–organic frameworks (SURMOFs) show promising behavior for a manifold of applications. As MOF thin films are often unsuitable for conventional characterization techniques, understanding their advantageous properties over their bulk counterparts presents a great analytical challenge. In this work, we demonstrate that MOFs can be grown on calcium fluoride (CaF(2)) windows after proper functionalization. As CaF(2) is optically (in the IR and UV/Vis range of the spectrum) transparent, this makes it possible to study SURMOFs using conventional spectroscopic tools typically used during catalysis or gas sorption. Hence, we have measured HKUST‐1 during the adsorption of CO and NO. We show that no copper oxide impurities are observed and also confirm that SURMOFs grown by a layer‐by‐layer (LbL) approach possess Cu(+) species in paddlewheel confirmation, but 1.9 times less than in bulk HKUST‐1. The developed methodology paves the way for studying the interaction of any adsorbed gases with thin films, not limited to MOFs, low temperatures, or these specific probe molecules, pushing the boundaries of our current understanding of functional porous materials.